2014
DOI: 10.1590/s1517-83822014000200033
|View full text |Cite
|
Sign up to set email alerts
|

Search for endophytic diazotrophs in barley seeds

Abstract: Eight endophytic isolates assigned to Pseudomonas, Azospirillum, and Bacillus genera according to pheno-genotypic features were retrieved from barley seeds under selective pressure for nitrogen-fixers. Genetic relationships among related isolates were investigated through RAPD. Six isolates displayed nitrogen-fixing ability, while all could biosynthesize indolacetic acid in vitro and showed no antibiosis effects against Azospirillum brasilense Az39, a recognized PGPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…From all identified tef seed endophytic bacterial strains, majority of them are belonged to genus Pseudomonas, some of the endophytes belonged to genus Pantoae and Enterobacter, whereas few of them belonged to genus Bacillus, Serratia and Razobium. The present study result was correlated with the previous work of Zawoznik [17], he reported that eight endophytic bacteria isolates assigned as Pseudomonas, Azospirillum, and Bacillus genera were isolated from barley seeds under selective pressure for nitrogen-fixing bacteria. For a biotic environmental stress condition, salinity is one of the major factors that adversely affect crops production and productivity in the world.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From all identified tef seed endophytic bacterial strains, majority of them are belonged to genus Pseudomonas, some of the endophytes belonged to genus Pantoae and Enterobacter, whereas few of them belonged to genus Bacillus, Serratia and Razobium. The present study result was correlated with the previous work of Zawoznik [17], he reported that eight endophytic bacteria isolates assigned as Pseudomonas, Azospirillum, and Bacillus genera were isolated from barley seeds under selective pressure for nitrogen-fixing bacteria. For a biotic environmental stress condition, salinity is one of the major factors that adversely affect crops production and productivity in the world.…”
Section: Discussionsupporting
confidence: 91%
“…Johnston-Monje and Raizada [16] reported that most of the bacterial isolates from seeds of different maize varieties were able to solubilize phosphorus and fix nitrogen. In addition, Zawoznik [17] reported that eight endophytic bacteria designated to Pseudomonas, Azospirillum, and Bacillus genera were isolated from barley seeds under selective pressure for nitrogen-fixing bacteria.…”
Section: Introduction Background and Justificationmentioning
confidence: 99%
“…Species participating in our biofertilizer consortium, such as Serratia liquefaciens (Kalbe et al 1996) and Stenotrophomonas maltophilia (Berg et al 1996), are known as beneficial rhizobacteria. Pseudomonas putida (Zawoznik et al 2014) and most species of Serratia (Kalbe et al 1996) secrete IAA, which can directly promote root growth. Several recent studies have demonstrated also beneficial effects for plants, shown by quorum sensing molecules, in particular the N-acyl homoserine lactone group produced by different Gram-negative bacteria (reviewed in Schikora et al 2016) such as S. liquefaciens and P. putida (Schuhegger et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The seed microbiome is increasingly attracting interest, and has been the subject of several recent reviews [ 7 , 41 , 42 , 43 ]. Bacteria have been detected in surface-sterilized seeds of various species, including crop plants like alfalfa [ 44 ], rice [ 25 , 45 , 46 , 47 , 48 , 49 ], maize [ 50 , 51 ], tobacco [ 52 ], coffee [ 53 ], quinoa [ 54 ], common bean [ 55 ], grapevine [ 56 ], barley [ 57 ], and pumpkin [ 58 ], but also in wild plants like the giant cardon cactus ( Pachycereus pringlei ) [ 59 ], annual ryegrass ( Lolium rigidum ) [ 60 ], various species of eucalyptus ( Eucalyptus spp.) [ 61 ], Norway spruce ( Picea abies ) [ 62 ], and the South American tree Anadenanthera colubrina [ 63 ].…”
Section: Vertical Transmissionmentioning
confidence: 99%